Malaysia’s ratification of the UN convention on the rights of persons with disabilities (UN CRPD) - Mokhtar, Khairil Azmin; Md Tah, Ikmal Hisham (IJBEL, 2016)
Marginalization and discrimination of Persons with Disabilities (PWD) by a certain segment of societies are common problems in many countries mainly due to lack of legal measures in addressing the problems. This is one of the main factors that leads to the creation by the UN of the Convention on the Rights of Persons with Disabilities and the Optional Protocol (UN CRPD) in 2006. The treaty is significant due to various reasons and one of them is because it shifts the promotion and protection of the rights of people with disabilities from medical or charity model towards social model which adopts human rights based approach. This approach has become recent phenomena in international law which have been used by jurisdictions all over the world. As a member of the international community, Malaysia became a signatory of the UN CRPD in 2008 and later ratified it in 2010. The commitment was the impetus for the enactment of the PWD Act 2008. Malaysia, however, has made reservations on two main articles of the CRPD namely Article 15 (freedom of torture or cruel, inhuman or degrading treatment or punishment) and Article 18 (liberty of movement and nationality). It also does not sign the Optional Protocol which allows individual and groups complaint to the CRPD Committee for any breach occurred. This paper analyzes Malaysian’s compliance with the rules and obligations under the UN CRPD. The Report of Roundtable Discussion on Removing Reservations of International Conventions (CEDAW, CRC & CRPD) from the Human Rights Commission of Malaysia (SUHAKAM) will be referred as part of the duty of SUHAKAM to ensure government’s compliance with international human rights treaty. It is concluded that the reservation of the articles should be removed to ensure better progress of development on human rights in Malaysia.